The developing role of Islamic banking and finance from local to global perspectives - Bisisu, Fu'ad Hamdi, 1943- (Emerald, 2014)
This volume is designed to present a conceptual and practical illustration for the contemporary developing role of Islamic banking and finance components including Islamic banking, Non Islamic banking (Takaful and Financial Markets Tools and Products) with stronger focus directed to the regulatory aspects, country, regional case studies and International Financial Crisis impacts.Consequently this volume defines how public policies, governance, legal framework and field studies' lessons can help decision makers to identify the major factors that may shape the attitude of both Islamic Financial Institutions and customers towards safe and sound services and through defining main determinants for successful, strategic inclusion of the Islamic Financial System into real sustained development nationally, regionally and internationally.
Includes indexes.
Keywords: Banks and banking -- Religious aspects -- Islam.; Banks and banking -- Islamic countries.; Finance -- Islamic countries.; Finance -- Religious aspects -- Islam.; elektronické knihy; electronic books